Anti-inflammatory and anti-microbial activities of aqueous leaves extract of Butea frondosa - Amit Gupta; Sushama R Chaphalkar (Shahrekord University of Medical Sciences, 2016)
Introduction: Butea frondosa has been suggested to be very useful in treating inflammatory diseases but no scientific investigation has been done in such direction. In this study the anti-inflammatory and anti-microbial activities of leaves aqueous extract of B. frondosa were determined in infected and non-infected human whole blood against specific vaccine antigen, HBsAg.Methods: In order to explore the anti-inflammatory and anti-microbial activities of B. frondosa (0.5-0 mg/mL; 50 μl), infected (virally) and non infected (control) human whole blood samples were stimulated with hepatitis B vaccine containing surface antigen (HBsAg, 20 μg/mL;10 μl) in order to determined its blood counts and proliferation assay.Results: Aqueous leaves extract of B. frondosa (10 mg/mL; 50 μl) containing HBsAg inhibited the percentage count of monocytes as well as granulocytes population in both cases. In addition, this aqueous extract also reduced its proliferation rate at higher doses.Conclusion: Aqueous leaves extract of B. frondosa possesses both anti-inflammatory and antimicrobial activities and might be used for these purposes.